Student Perceptions of Cheating Behavior Reviewed from Tauhid Character Values at Djuanda University - Rachmah Amalia; Annissa Mawardini; Shofia Hanna Nisa; Siti Nurul Zalzilah; Fajriatunnisa Fajriatunnisa (PALAPA, 2024)
The research uses a qualitative research design to determine students' perceptions of cheating behavior regarding the tauhid character value at Djuanda University. Using thematic analysis, data was obtained through questionnaires distributed to 30 students from the Primary School Teacher Education (PGSD), Islamic Education Management (MPI), and Law study programs. The research results obtained three categories: forms of violations, causal factors, and solutions to handle cheating habits. The research concluded that in the students' view, cheating behavior is a form of breach of honesty, which lies in a person's intentions, promises, and activities. The leading solution taken by students to deal with cheating behavior is to apply the tauhid character values ​​of integrity, honesty, responsibility, and self-awareness in every activity. This research contributes to fostering tauhid character values ​​to overcome all acts of academic dishonesty.